Multiple dichotomies in timbre research - PAPANIKOLAOU, George; PASTIADIS, Constantinos (Archives of Acoustics, 2009)
In this paper an overview of aspects, terminology and literature on contemporary research regarding timbre is presented. Timbre is a multidimensional entity, and research traces its multifaceted nature. The paper handles this structural complexity using a domain-task-results paradigm. Several domains of application are examined and various aspects of timbre questioning are outlined, although consideration of aspects in music and its contextual applications are postponed for a following detailed report for reasons of presentation compactness and extent. A self-evident differentiation of research categorization stems from the type of consideration of timbre as a perceptual attribute or as a manifestation of physical (either generative or modified after transmission) phenomena and processes. As more "axes" of differentiation also emerge, this work attempts to highlight issues that rise and propose possible research directions.